1979
DOI: 10.1093/ajcn/32.9.1776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a vigorous walking program on body composition, and carbohydrate and lipid metabolism of obese young men

Abstract: With no attempt made to influence their diet, six sedentary obese men ages 19 to 31 completed 16 weeks of vigorous walking 90 min, 5 days/week, on a treadmill at up to 3.2 mph on a 10% grade, expending about 1100 kcal per session. Body composition studies indicated a loss of 5.9 kg of body fat and a gain of 0.2 kg of lean tissue for a net loss of 5.7 kg. Percentage body fat decreased from 23.3 to 17.4. Monitored food intake initially increased, then progressively decreased below pretraining levels. Work capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
7

Year Published

1982
1982
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(44 citation statements)
references
References 36 publications
1
34
2
7
Order By: Relevance
“…This is in agreement with the ®ndings of Leon et al where insulin was reduced by 43% in males after 16 weeks of walking which resulted in a 6% decrease in body weight. 43 The changes in the present study and in the study of Leon are not remarkably different from the ®ndings of Franssila-Kallunki et al, where an 11% decrease in weight was shown in response to VLED and fasting insulin decreased 43% and insulin area under the curve analysis in response to a test meal decreased 21%. Thus, exercise in the current study was associated with changes in metabolic ®tness which compare to studies using more aggressive therapies and in which weight loss was greater.…”
Section: Discussioncontrasting
confidence: 66%
“…This is in agreement with the ®ndings of Leon et al where insulin was reduced by 43% in males after 16 weeks of walking which resulted in a 6% decrease in body weight. 43 The changes in the present study and in the study of Leon are not remarkably different from the ®ndings of Franssila-Kallunki et al, where an 11% decrease in weight was shown in response to VLED and fasting insulin decreased 43% and insulin area under the curve analysis in response to a test meal decreased 21%. Thus, exercise in the current study was associated with changes in metabolic ®tness which compare to studies using more aggressive therapies and in which weight loss was greater.…”
Section: Discussioncontrasting
confidence: 66%
“…188,189 However, in the trial reviewed here, it was also found to be associated with a significantly increased risk of falling.…”
Section: Associated Effectsmentioning
confidence: 72%
“…Leon et al 46 studied six sedentary obese men aged 16-31 years who completed 16 weeks of 90 min vigorous walking, 5 days/week, on a treadmill at up to 5.2 km/h on a 10% grade, expending about 1100 kcal per session. Physical work capacity was assessed by means of the modified Balke multistage treadmill exercise test protocol.…”
Section: Effects Of Long-term Exercise On Food Intake In Lean and Obementioning
confidence: 99%